The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3171/2018.8.jns181217
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumor growth via IGFBP3 depletion as a potential treatment in glioma

Abstract: OBJECTIVEDespite intensive medical treatment, patients with glioblastoma (grade IV glioma [GBM]) have a low 5-year survival rate of 5.5%. In this study, the authors tried to improve currently used therapies by identification of a therapeutic target, IGFBP3, for glioma treatment.METHODSIGFBP3 RNA expression in 135 patients newly diagnosed with glioma was correlated with clinicopathological factors. Immunohistochemical analysis was performed to determine IGFBP3 protein expression in glioma specimens. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 30 publications
1
28
0
1
Order By: Relevance
“…Like CYR61, overexpression of WNT16B promoted tumor growth and chemotherapy resistance [26]. Depletion of IGFBP3 [27] or NT5E [28] induced tumor cell loss and thereby suppressed tumor cells growth. Of contrast, in vitro and in vivo experiments suggested overexpression of GDF15 [29] or CARD16 [30] inhibited tumor cell growth via controlling caspases and cell proliferation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Like CYR61, overexpression of WNT16B promoted tumor growth and chemotherapy resistance [26]. Depletion of IGFBP3 [27] or NT5E [28] induced tumor cell loss and thereby suppressed tumor cells growth. Of contrast, in vitro and in vivo experiments suggested overexpression of GDF15 [29] or CARD16 [30] inhibited tumor cell growth via controlling caspases and cell proliferation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, transcriptional profiling and network analysis of R vs. NR neurosphere lines identified additional differentially-expressed gene networks. Within these, two genes, IGFBP3 and IGFBP5, belonging to the IGF-1 signaling pathway, have been previously implicated in tumorigenesis 36,37 including GBM 38 . IGFBPs can drive tumorigenesis by increasing IGF-dependent signaling that in turn increases cancer cell proliferation and survival 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The tumor promoting properties of IGFBP-3 are linked to its ability to increase STAT-1 expression that, in turn, result associated with reduced patients overall survival (OS) ( 57 ). Furthermore, Chia-Hua Chen demonstrated that IGFBP-3 silencing suppresses glioma cell proliferation by G2/M cell cycle arrest ( 58 ). On the contrary, the anti-tumorigenic and anti-angiogenetic functions of IGFBP-4 in glioma cells depend to its ability to induce dibutyryl cyclic AMP (dB-cAMP) that antagonize the VEGFs action in an IGF-independent manner ( 59 ).…”
Section: The Igf Signaling Pathway In Gbmmentioning
confidence: 99%